Persepsi Pegawai Terhadap Program Reward Di Seksi Pelayanan Primer Dinas Kesehatan Provinsi Sumatera Utara - Hasibuan, Rapotan; Andini, Zahra; H Sihotang, Oryza Sativa; Rahma Dilla, Nur Indah; Hasibuan, Nadhilah; Amanda Azwa, Nadia; Marpaung, Assyifa Deswita (JUKEJ : Jurnal Kesehatan Jompa, 2025)
The perception of primary service personnel towards the reward plan initiated by the Head of Section at the North Sumatra Provincial Health Office is important in understanding the effectiveness of work motivation policies in the government environment. This study aims to determine how primary service personnel view and assess the reward plan initiated by leaders as an effort to improve employee performance. This study uses a qualitative method with a descriptive approach. There were five informants, who were selected using purposive sampling based on certain criteria such as length of service, knowledge of the reward program, and willingness to provide information. Data were obtained through in-depth interviews, non-participatory observation, and documentation, then analyzed using the Miles and Huberman model, which includes data reduction, data presentation, and conclusion drawing and verification. The results of the study show that most employees have a positive perception of the reward plan because it is considered to increase work enthusiasm and productivity. However, some also expressed concerns that an overly competitive system could create pressure and reduce motivation. The success of the reward program is highly dependent on fairness, transparency of assessment, and empathetic communication between leaders and staff. In conclusion, the fair and transparent implementation of rewards can increase the motivation and loyalty of primary service personnel in supporting the achievement of organizational goals at the North Sumatra Provincial Health Office.